THE EFFECTIVENESS OF COUNTER PRESSURE/DEEP BACK MASSAGE IN REDUCING PAIN LEVELS IN PARTICULAR WOMEN - Ermiati, Ermiati; Nusaibah, Niken; Aulia, Santi; Cahyani, Gita; Rahmawati, Yuli; Dwi, Yasmina; Handayani, Nathasa; Nabilla, Salsabila; Srimurni, Nita Ayu (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
During labor, myometrial contractions can be painful. Labor pain is an unpleasant process and can increase uncoordinated uterine activity and prolong the labor process thereby endangering the life of the fetus and mother. Non-pharmacological efforts to reduce pain can use counter pressure/deep back massage techniques by placing pressure on the back pain area or sacrum. This study aims to determine the effectiveness of counter pressure/deep back massage in reducing pain levels in mothers giving birth based on literature analysis. The method used is a narrative review through searches from the PubMed, Garuda and Science Direct databases. Review articles using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method with 4 stages, namely identification, screening, feasibility, and acceptable results. The search results identified 579 articles, then they were screened and 32 articles were found, then at the feasibility stage 7 articles were found and it was decided that these 7 articles could be accepted. The results of the article review found that counter pressure massage and deep back massage can stimulate the body to release endorphins which act as pain relievers and provide a relaxing condition for the mother, thereby increasing circulation in the genital area and improving cervical elasticity. In conclusion, counter pressure massage and deep back massage are effective in reducing the pain level of women giving birth during the first active phase. Counter pressure massage is considered more effective than deep back massage.